Urinary cadmium levels predict mortality of patients with acute heart failure - Hsu CW; Weng CH; Lee CC; Lin-Tan DT; Chu PH; Chen KH; Yen TH; Huang WH (Dove Medical Press, 2017)
Ching-Wei Hsu,1–3 Cheng-Hao Weng,1–3 Cheng-Chia Lee,1–3 Dan-Tzu Lin-Tan,1–3 Pao-Hsien Chu,3,4 Kuan-Hsing Chen,1–3 Tzung-Hai Yen,1–3 Wen-Hung Huang1–3 1Department of Nephrology, Division of Clinical Toxicology, Chang Gung Memorial Hospital, Taipei, Taiwan, ROC; 2Department of Nephrology, Division of Clinical Toxicology, Linkou Medical Center, Taoyuan, Taiwan, ROC; 3Chang Gung University and School of Medicine, Taoyuan, Taiwan, ROC; 4Division of Cardiology, Chang Gung Memorial Hospital, Linkou Medical Center, Taoyuan, Taiwan, ROC Background: Acute heart failure (AHF) is a serious condition that is associated with increased mortality in critically ill patients. Previous studies indicated that environmental exposure to cadmium increases mortality of general populations. However, the relationship of cadmium exposure and mortality is unclear for AHF patients.Materials and methods: A total of 153 patients with AHF in intensive care units (ICUs) met the inclusion criteria and were followed up for 6 months. Demographic data, AHF etiology, hematological and biochemical data, and hospital mortality were recorded. The scores of two predictive systems (Sequential Organ Failure Assessment [SOFA], Acute Physiology and Chronic Health Evaluation II [APACHE II]) for mortality in critically ill patients were calculated, and urinary cadmium levels were recorded.Results: At the end of the follow-up period, the mortality rate was 24.8%. The survivors (n=115) had higher urinary cadmium levels on day 1 (D1UCd) of ICU admission than non-survivors (n=38). A multiple linear regression analysis revealed a positive correlation between D1UCd and acute kidney injury, but a negative correlation between D1UCd and the level of serum albumin. A multivariate Cox analysis indicated that D1UCd was an independent predictor of mortality in AHF patients. For each increment of 1 µg of D1UCd, the hazard ratio for ICU mortality was 1.20 (95% confidence interval [CI]: 1.09–1.32, P<0.001). The area under the receiver operating characteristic curve for D1UCd was 0.84 (95% CI: 0.78–0.91), better than the values for the SOFA and APACHE II systems.Conclusion: The D1UCd may serve as a single predictor of hospital mortality for AHF patients in the ICU. Because of the high mortality and smaller sample size, more investigations are required to confirm these observations and elucidate the underlying mechanisms. Keywords: acute heart failure, cadmium, intensive care unit, hospital mortality